The chemical constituents of the stem bark and roots of goniothalamus tomentosus (Annonaceae) - Hasliza Yusof,; Laily Din,; Zuriati Zakaria ,; Kamarudin Mat Salleh, (Universiti Kebangsaan Malaysia, 2004)
A new species from the Goniothalamus genus, G. tomentosus, was investigated. Two alkaloids, aristololactam BII 1 and ouregidione 2 together with a stigmasterol isolated from the stem bark and roots were identified using spectroscopic techniques.